Peningkatan Kesehatan Masyarakat di Masa Pandemi Bagi Warga Panti Asuhan di Surabaya - Khusnul Fikriyah; Rachma Indrarini; Sri Abidah Suryaningsih; Nurul Hanifah; Clarashinta Canggih (Universitas Lancang Kuning, 2021)
This Community Service (PKM) activities is based on the condition of the orphanage which is inhabited by many people. Maintaining health is very important while living and interacting with many people during the Covid-19 Pandemic. One of the efforts to maintain health is by implementing personal hygiene so we are not become a virus carrier for other people. Based on the recommendation of WHO and also the Surabaya City Government, residents are asked to implement a clean and healthy lifestyle (PHBS). This PKM aimed to provide information to the community, particularly who lives in orphanage, about efforts to live a clean and healthy lifestyle and provide vitamins and foodstuffs to maintain and improve the personal health of the residents of the orphanage. The implementation of this Community Service activity took place from June-October 2020. With the implementation of this activity, it was found that there was an increase in the understanding of the orphanage about clean and healthy living habits. In addition, it is hoped that in the long term, the residents of the orphanage will be more concerned with personal hygiene and also apply health protocols in their daily lives so that they can break the chain of transmission of the Covid 19 pandemic